24.1k views
3 votes
Make b the subject of the formula

k = (brt)/(v - b)


1 Answer

3 votes

Answer:

b =
(kv)/(k+rt)

Explanation:

Given

k =
(brt)/(v-b) ← multiply both sides by (v - b)

k(v - b) = brt ← distribute left side

kv - kb = brt ( subtract brt from both sides )

kv - kb - brt = 0 ( subtract kv from both sides )

- kb - brt = - kv ( multiply through by - 1 to clear the negatives )

kb + brt = kv ← factor out b from each term on the left

b(k + rt ) = kv ← divide both sides by (k + rt )

b =
(kv)/(k+rt)

User Paul Hanbury
by
4.5k points